The Transcription Factor C/EBP-β Mediates Constitutive and LPS-Inducible Transcription of Murine SerpinB2 - Udofa, Ekemini A. (Public Library of Science, 2013)
SerpinB2 or plasminogen activator inhibitor type 2 (PAI-2) is highly induced in macrophages in response to inflammatory stimuli and is linked to the modulation of innate immunity, macrophage survival, and inhibition of plasminogen activators. Lipopolysaccharide (LPS), a potent bacterial endotoxin, can induce SerpinB2 expression via the toll-like receptor 4 (TLR4) by ∼1000-fold over a period of 24 hrs in murine macrophages. To map the LPS-regulated SerpinB2 promoter regions, we transfected reporter constructs driven by the ∼5 kb 5'-flanking region of the murine SerpinB2 gene and several deletion mutants into murine macrophages. In addition, we compared the DNA sequence of the murine 5′ flanking sequence with the sequence of the human gene for homologous functional regulatory elements and identified several regulatory cis-acting elements in the human SERPINB2 promoter conserved in the mouse. Mutation analyses revealed that a CCAAT enhancer binding (C/EBP) element, a cyclic AMP response element (CRE) and two activator protein 1 (AP-1) response elements in the murine SerpinB2 proximal promoter are essential for optimal LPS-inducibility. Electrophoretic mobility shift (EMSA) and chromatin immunoprecipitation (ChIP) assays demonstrated that LPS induces the formation of C/EBP-β containing complexes with the SerpinB2 promoter. Importantly, both constitutive and LPS-induced SerpinB2 expression was severely abrogated in C/EBP-β-null mouse embryonic fibroblasts (MEFs) and primary C/EBP-β-deficient peritoneal macrophages. Together, these data provide new insight into C/EBP-β-dependent regulation of inflammation-associated SerpinB2 expression.